Respuestas

2012-10-10T05:36:43+02:00
2012-10-10T05:52:15+02:00

     3 X - 4 Y = 13  despejo  X            13 + 4 Y       3 - 3 Y                            3 - 3 Y

        3 X = 13 + 4 Y                         =======  =   =========                 X = ======

                13 + 4 Y                              3                   2                                 2

           X= =======                                                                                

                    3                               2 * ( 13 + 4 Y ) = 3 * ( 3 - 3 Y )      

                                                                                                             3 - 3* -1

                                                          26 + 8 Y = 9 - 9 Y                     X = =======

     2 X + 3 Y = 3                                     8 Y + 9 Y =  9 - 26                          2

         2 X = 3 - 3Y

                  3 - 3 Y                                    17 Y = - 17                               3 + 3

           X =   =====                                        Y = -17/17                     X = ======

                     2                                            Y = -1                                       2

 luego igualo                                                                                     X = 6 / 2 = 3

                                                                                                        X = 3

 

luego pruebo valores de X = 3     y    Y = -1

 

3 x - 4 Y = 13

3*3 - 4*-1 = 13

9 + 4 = 13

    13 = 13